THE EFFECT OF CUPPING THERAPY ON LOW BACK PAIN LITERATURE REVIEW - Novira Parawansa; Nadya Anggun Pertiwi; Fariza Hasyati; Tilka Rahmatia Quddusi; Indri Seta Septadina (International Islamic Medicine Forum, 2020)
The World Health Organisation (WHO) defined low back pain (LBP) as pain or discomfort that is localized between the costal margin and above the inferior gluteal folds, with or without leg pain. In the world, it is estimated that the prevalence of LBP ranges from 1.4% to 20.0%. In 2013, around 24.7% of workers in Indonesia had experienced occupational diseases caused by low back pain. Based on the Riset Kesehatan Dasar (RKD) survey pada in 2018, 31.4% of Indonesians have used traditional medicine, with manual treatment skill, the type of traditional medicine effort, most widely used (65.3%) and one of it is cupping therapy. Cupping (therapy) also named Hijamah. Cupping therapy is one of the alternative medicines that uses vacuum cups on the cupping point of the skin surface. Although the mechanism of action of cupping therapy is still unclear, there are several reported effects of cupping therapy including increasing skin blood flow, changing skin biomechanical properties, increasing the pain threshold, increasing local anaerobic metabolism, reducing inflammation, and modulating the immune system. cellular. According to research conducted by Volpato et al. (2019) demonstrated the effectiveness of cupping therapy in reducing pain perception and improving function in individuals with low back pain.